CIVIL LEGAL PROTECTION FOR VIOLATIONS OF COPYRIGHT LICENSE AGREEMENTS REVIEWED FROM THE CIVIL CODE AND LAW NUMBER 28 OF 2014 CONCERNING COPYRIGHT - Muhammad Dyo Febriza; Surahmad (RADJA PUBLIKA, 2026)
A copyright licensing agreement serves as a legal instrument enabling the utilization of economic rights over a work without transferring its ownership; however, its implementation remains susceptible to infringements in the form of breach of contract and unlawful acts. This study aims to analyze the forms of infringement that may arise within a copyright licensing agreement and to examine the legal protections available to the parties under the Indonesian Civil Code ( KUHPerdata ) and Law Number 28 of 2014 on Copyright, referencing Case No. 853/ Pdt.G /2024/PN JKT.SEL jo. No. 1338/PDT/2025/PT DKI as an illustrative case. This study employs a normative legal research method with a statutory and conceptual approach. The findings indicate that infringements in a copyright licensing agreement can be qualified as a breach of contract if the licensee fails to pay royalties or exceeds the agreed scope of the license, and as an unlawful act if unauthorized sublicensing occurs, as explicitly prohibited by Article 81 of the Copyright Law. The available legal protection is multi-layered — the Civil Code provides a general framework through Articles 1243, 1365, 1266, and 1267, while the Copyright Law as lex specialis offers preventive protection through mandatory license registration at DJKI and repressive protection via lawsuits filed with the Commercial Court relating to Article 96 jo. Article 99. These two legal instruments are not substitutes for one another, but rather operate complementarily. Understanding the relationship between them is expected to serve as a reference for parties in copyright licensing agreements in determining the most effective legal protection strategy.